Paracoccidioidomycosis in wild and domestic animals - Neves, Sandra Leite (2006)
Paracoccidiodomycosis is the most prevalent systemic mycosis in Latin América, mainly in Brazil. Although many studies have been done about the pathology and diagnosis of this mycosis little is known about the eco-epidemiology of the etiological agent Paracoccidioides brasiliensis. The fungus habitat also is unknown although is thought that the fungus lives as a saprobe in soil. The participation of other animal species in P. brasiliensis ecology is poorly understood and fungus isolation from animals as bat and penguin were not reproducible. The armadillos Dasypus novencinctus probably play a role in the fungus eco-epidemiology taking into account that several isolates were obtained from these animals. Seroepidemiologic studies have shown that dogs are infected by P. brasiliensis mainly in rural areas and recently was reported the first case o natural paracoccidioidomycosis in dogs. The role of other animal species in the eco-epidemiology of P. brasiliensis remains doubtful.